The dentition: the outcomes of morphogenesis leading to variations of tooth number, size and shape. (20th March 2014) - Brook, AH; Jernvall, J; Smith, RN; Hughes, TE; Townsend, GC
Abstract: The clinical importance of variations of tooth number, size and shape is seen in many dental disciplines. Early diagnosis allows optimal patient management and treatment planning, with intervention at an appropriate time to prevent complications in development and so reduce later treatment need. Understanding the process of dental morphogenesis and the variations in outcomes is an important contribution to the multidisciplinary clinical team approach to treatment. Tooth number, size and shape are determined during the initiation and morphogenetic stages of odontogenesis. The molecular evidence of repetitive signalling throughout initiation and morphogenesis is reflected clinically in the association of anomalies of number, size and shape. This association has been statistically modelled from epidemiological evidence and confirmed by 2D and 3D measurement of human dental study casts. In individuals with hypodontia, the teeth that are formed are smaller than the population mean and often show reduced and simplified shape. In contrast, in individuals with supernumerary teeth, the other teeth are larger than average and may show an enhanced shape. Clinical observations in humans and studies of laboratory animals gave rise to the concept of morphogenetic fields within the dentition. The findings, which can also be considered as reflecting gene expression territories, have been developed to incorporate field, clone and homeobox theories. The clinical distribution of developmental anomalies tends to follow the pattern of these fields or territories. Improved care for patients with these anomalies will come not only from utilizing a multidisciplinary clinical team but also by expanding the approach to include other relevant scientific disciplines.